2020
DOI: 10.18632/aging.103166
|View full text |Cite
|
Sign up to set email alerts
|

Sigma-1 receptor is involved in diminished ovarian reserve possibly by influencing endoplasmic reticulum stress-mediated granulosa cells apoptosis

Abstract: Sigma non-opioid intracellular receptor 1 (sigma-1 receptor), a non-opioid transmembrane protein, is located on cellular mitochondrial membranes and endoplasmic reticulum. Current research has demonstrated that sigma-1 receptor is related to human degenerative diseases. This study is focused on the effects of sigma-1 receptor on the pathophysiological process of diminished ovarian reserve (DOR) and granulosa cells (GCs) apoptosis. Sigma-1 receptor concentration in follicular fluid (FF) and serum were negativel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 93 publications
0
4
0
Order By: Relevance
“…TIRF imaging demonstrated that no Sig1R-YFP could be detected in the plasma membrane, and the expression in the peripheral areas of cells was low ( Fig 2 ). The Sig1R agonist PRE-084 at a concentration of 10 μM, which have been found to be optimal for the activation of Sig1R [ 29 , 30 ], did not cause substantial changes in the localization of Sig1R-YFP within the cells ( Fig 2 and S1 Fig ). No other agonist-dependent changes in Sig1R-YFP localization were detected.…”
Section: Resultsmentioning
confidence: 91%
“…TIRF imaging demonstrated that no Sig1R-YFP could be detected in the plasma membrane, and the expression in the peripheral areas of cells was low ( Fig 2 ). The Sig1R agonist PRE-084 at a concentration of 10 μM, which have been found to be optimal for the activation of Sig1R [ 29 , 30 ], did not cause substantial changes in the localization of Sig1R-YFP within the cells ( Fig 2 and S1 Fig ). No other agonist-dependent changes in Sig1R-YFP localization were detected.…”
Section: Resultsmentioning
confidence: 91%
“…A meta-analysis of 46 trials, including 19 trials of women with POR, showed that DHEA treatment is associated with improved pregnancy rates in POR patients, whereas clomiphene or letrozole use is not recommended [155]. DHEA, which signals through multiple neurotransmitter receptors, steroid receptors, and the sigma non-opioid intracellular receptor 1, may improve ovarian reserve, oocyte quality, and pregnancy rates in women with diminished ovarian reserve or premature ovarian aging [156]. Another promising strategy for enhancing IVF outcomes is the intraovarian injection of autologous platelet-rich plasma (PRP), which has been shown to increase antral follicle count and serum AMH levels in POI patients [157][158][159][160] and restore menstruation in patients who lacked a menstrual cycle for over a year [161].…”
Section: Adjunct Interventionmentioning
confidence: 99%
“…However, if ER stress is persistent or severe, UPR can alternatively activate proapoptotic programs (Kim et al, 2008). In GCs, ER chaperone glucose‐regulated protein 78 kDa initiated the protein kinase RNA‐like ER kinase/eukaryotic initiation factor 2α, inositol‐requiring enzyme 1α/X‐box‐binding protein, and activating transcription factor pathways (Jiang et al, 2020; Li et al, 2019; Lin et al, 2012; Xu, Pan, et al, 2021). Activation of these pathways contributed to induce GC apoptosis and increase expression of the enhancer‐binding protein homologous protein (CHOP) (He et al, 2016).…”
Section: Mechanisms Underlying Apoptosis Of Gcsmentioning
confidence: 99%